PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE AZARINE PADA MAHASISWI POLITEKNIK NEGERI UJUNG PANDANG - Khafifah, Nurul; Mawardi, Mawardi; Paramaudia, Paramudia (Journal of Business Administration (JBA), 2024)
This study aimed to determine the effect of promotion and price on purchasing decisions for Azarine skincare products among female students at Ujung Pandang State Polytechnic. The sampling technique used purposive sampling with a total of 97 respondents. Data analysis used  descriptive analysis using IBM SPSS 25 where the tests used are validity and reliability tests, classical assumption tests. The hypothesis in this research is an associative hypothesis where the tests used are multiple linear regression analysis, t test, f test and analysis of the coefficient of determination.The results of this study were: (1) promotions had a positive effect on purchasing decisions with a sig 0.00 < 0.05 and t value 7.259 > 1.985. (2) Price had a positive effect on purchasing decisions with a sig 0.02 < 0.05 and t value 3.225 > 1.985. (3) promotion and price simultaneously had a positive effect on purchasing decisions with a significance level of 0.00 < 0.05,  F-value 62.188 > 3.092 and the R-Square  47, 4%.